Traditions of the Bible : a guide to the Bible as it was at the start of the common era - Kugel, James L. (Harvard University Press, 1998)
James Kugel's The Bible As It Was (1997) has been welcomed with universal praise. Here now is the full scholarly edition of this wonderfully rich and illuminating work, expanding the author's findings into an incomparable reference work.Focusing on two dozen core stories in the Pentateuch--from the Creation and Tree of Knowledge through the Exodus from Egypt and journey to the Promised Land--James Kugel shows us how the earliest interpreters of the scriptures radically transformed the Bible and made it into the book that has come down to us today. Kugel explains how and why the writers of this formative age of interpretation--roughly 200 B.C.E. to 150 C.E.--assumed such a significant role. Mining their writings--including the Dead Sea Scrolls, works of Philo and Josephus and letters of the Apostle Paul, and writings of the Apostolic Fathers and the rabbinic Sages--he quotes for us the seminal passages that uncover this crucial interpretive process.For this full-scale reference work Kugel has added a substantial treasury of sources and passages for each of the 24 Bible stories. It will serve as a unique guide and sourcebook for biblical interpretation.